Implementasi SETS (Science Environment Technology and Society) Pada Pembelajaran IPA SD Berbasis Inquiryterhadap Berpikir IlmiahSiswa Kelas 4 SD Al-Irsyad Madiun - Raras Setyo Retno; Dyan Marlina (Universitas Sebelas Maret, 2018)
This study aims to find out how far students are able to apply the SETS approach on inquiry-based IPA learning. Through the SETS approach students are conditioned to be willing and able to apply the science principles to produce technological work followed by thoughts to reduce or prevent possible negative impacts that may arise from the emergence of this technology product to the environment and society based on the principle of inquiry. This SETS application is about scientific thinking so it is expected to improve scientific thinking science. In this class action research, the data analysis technique used is descriptive qualitative. Qualitative descriptive analysis is done by interactive analysis. Analysis of scientific thinking through multiple cycles. While the analysis of qualitative description with interactive analysis consists of data reduction, data presentation, and conclusion is done in an interactive form with data collection as a cycle process. The results showed pre cycle 28,44%, then at cycle I 52,33%, and at cycle II 80,33% which mean SETS approach able to improve student's scientific thinking. There is a positive response to students with SETS approach means that science learning with hands-on experience can make students think critically in solving a problem.